PERILAKU KONSUMEN RUMAH MAKAN CEPAT SAJI STUDI KASUS DI ROCKET CHIKEN CABANG DIPONEGORO DAN KFC METOS PALANGKA RAYA - Nia Fitriani; Merrisa Octora (Prodi Sosiologi FISIP UPR, 2021)
Human behaviour is an attitude or habit that is formed from the results of the accumulated experience in the form of something that has been heard, seen, felt and done which is then simulated by the surroundings and circumstances. Symbolic interaction is a relationship that occurs naturally between humans in society and the relationship between society and individuals. The interactions that occur between individuals develop through the symbols they create. Social reality is a series of events that occur to several individuals in society. The interactions that are carried out between individuals take place consciously and are related to body movements, sounds, and body expressions, all of which have a purpose and are called symbols. Fast food restaurants are restaurants that serve / serve food and beverages in a relatively short time from ordering to serving to customers.